The effect of doxycycline on neuron-specific enolase in patients with traumatic brain injury: a randomized controlled trial - Noha O. Mansour; Mohamed A. Shama; Rehab H. Werida (SAGE Publishing, 2021)
Objective: We aimed to examine the effect of doxycycline on serum levels of neuron-specific enolase (NSE), a marker of neuronal damage in traumatic brain injury (TBI) patients. Methods: Patients were randomly assigned into two groups ( n  = 25 each) to receive either placebo or doxycycline (200 mg daily), with their standard management for 7 days. Results: NSE serum levels in the doxycycline and control groups on day 3 were 14.66 ± 1.78 versus 18.09 ± 4.38 ng/mL, respectively ( p  = 0.008), and on day 7 were 12.3 ± 2.0 versus 16.43 ± 3.85 ng/mL, respectively ( p  = 0.003). Glasgow Coma Scale (GCS) on day 7 was 11.90 ± 2.83 versus 9.65 ± 3.44 in the doxycycline and control groups, respectively ( p  = 0.031). NSE serum levels and GCS scores were negatively correlated ( r  = −0.569, p  < 0.001). Conclusion: Adjunctive early use of doxycycline might be a novel option that halts the ongoing secondary brain injury in patients with moderate to severe TBI. Future larger clinical trials are warranted to confirm these findings.